Carbon footprint of waste generated in orthopaedic cases in Pakistan: a pilot descriptive study - Muhammad Talal Ibrahim; Muhammad Salman; Faizan Khan; Samie Asghar Dogar; Shahryar Noordin (Journal of the Pakistan Medical Association, 2026)
Most of the literature on reducing carbon emissions is from the developed world, which does not represent the realities of the developing world. Therefore, the current study was planned to gauge the carbon footprint generated by total knee and hip arthroplasty at the Aga Khan University Hospital, Karachi, between November 2023 and July 2024. The trash was sorted into biohazardous, packaging, and discarded equipment categories. The institutional Carbon Management Tool was used to estimate the carbon footprint. Of the 45 cases, the mean total trash per case was 29.3±13.9kg. In the current practice, the mean carbon footprint was 26.3±12.5kg carbon dioxide equivalents per case. Packaging represented 14.0±4.2% of the total carbon footprint from the waste. Even if this waste is sent to landfill sites, the carbon footprint is not reduced, indicating that the zero-emission solutions from the developed world may not work well in low- and middleincome countries, and innovative local solutions are urgently required. Keywords: Carbon footprint, Greenhouse gasses, Hospital, Medical, Surgical, Pollution..